1988
DOI: 10.1021/ac00175a014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide measurement in seawater by (p-hydroxyphenyl)acetic acid dimerization

Abstract: The dimerization of (p-hydroxyphenyl)acetlc acid by hydrogen peroxide In the presence of peroxidase has been adapted to the determination of hydrogen peroxide In seawater. The fluorometrlc method presented requires only one mixed reagent for sample analysis and produces a stable product that does not require Immediate measurement. Changes In reaction stoichiometry resulting from naturally occurring organic material have been addressed. The detection limit, defined as 3 times the standard deviation of the blank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 32 publications
1
107
0
1
Order By: Relevance
“…Although a number of more sensitive analytical methods are available for the determination of hydrogen peroxide in seawater (Miller and Kester, 1988;Yuan and Shiller, 1999), these methods do not differentiate between hydrogen peroxide and other short chain organic peroxides.…”
Section: Peroxide Analysismentioning
confidence: 99%
“…Although a number of more sensitive analytical methods are available for the determination of hydrogen peroxide in seawater (Miller and Kester, 1988;Yuan and Shiller, 1999), these methods do not differentiate between hydrogen peroxide and other short chain organic peroxides.…”
Section: Peroxide Analysismentioning
confidence: 99%
“…The concentration of H 2 O 2 was determined using a fluorescent technique involving the enzyme catalysed dimerization of ( p-hydroxy-phenyl)acetic acid (POH-PAA) (Miller and Kester, 1988). This method measures the total peroxide in seawater; this includes organic peroxides as well as H 2 O 2 , the concentration of the organic peroxide can be determined separately by prior removal of the H 2 O 2 by the use of catalase.…”
Section: Determination Of H 2 Omentioning
confidence: 99%
“…This suggests that the catalytic activity of MnTSPc is lower than that of HRP because the reaction with H2O2 to form a dimer in the presence of HRP is completed in less 60 s. 11 An investigation also showed that the fluorescence intensity of the reaction product was constant for at least 6 h and only a slight decrease occurred after 48 h. This is quite contrary to the HRP-P-HPAA-H2O2 system, which shows a relatively large long-term increases in fluorescence due to the spontaneous dimerization of P-HPAA in the sample solution. 10,11 This may suggest that the spontaneous dimerization of P-HPAA in the presence of MnTSPc is weaker than that in the presence of HRP. It was noted that a slow decrease occurred with no change in the standard addition slope.…”
Section: Reaction Time and Temperaturementioning
confidence: 99%
“…9 The application of the fluorescent dimerization of p-hydroxyphenylacetic acid (P-HPAA) to environmental matrices offers some advantages over alternate methods and provides an analytically consistent method for a wide range of atmospheric and oceanic measurements of H2O2. 10 The fluorescent P-HPAA dimer is a stable product, which can be quantified by fluorescence several days after preparation, eliminating difficulties caused by the decomposition of peroxides in stored samples.11 Also, many of the interferences that plagued the early chemiluminescent methods do not occur with P-HPAA. 11,12 However, the P-HPAA method often employs two biological enzymes, horseradish peroxidase and catalase, which are both expensive and unstable.…”
mentioning
confidence: 99%
See 1 more Smart Citation